Comprehensive analysis of Nematode–Tomato Plant–Mycorrhizal Fungus system for bio based product development - Garita, Sebastián Andrés (2023)
Nacobbus aberrans is a plant parasitic nematode that causes significant economic losses in the American Continent and is considered a quarantine pest in many countries. Some arbuscular mycorrhizal fungi have shown the ability to reduce the population of this pathogen; however, most studies do not consider other relevant aspects that have to do with the crop or the fungus. The purpose of this work was to select an isolated mycorrhizal fungus based on a comprehensive analysis of the Nematode–Plant–Mycorrhizal Fungus system. The test was conducted on Solanum lycopersicum L. grown in pots. The evaluated isolates were Funneliformis mosseae, Rhizoglomus intraradices A2, and Rhizoglomus intraradices B1. All the isolates reduced the nematode population significantly; however, differences in the content of photosynthetic pigments, soluble proteins, and osmoregulatory metabolites were identified. All of these impacted on the photosynthetic rates of the different treatments. There were also differences in the growth of the fungi within the roots, and in the viability of the fungal structures. The comprehensive analysis of the plant–nematode–fungus group allows us to conclude that the isolate with the greatest capacity to compensate for the negative effect of parasitism, and with the greatest possibility of lasting as a biocon- trol agent is Funneliformis mosseae.